2021
DOI: 10.1080/15592324.2021.2021365
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of C-TERMINALLY ENCODED PEPTIDE (CEP) family in Brassica rapa L

Abstract: The small regulatory C-TERMINALLY ENCODED PEPTIDE (CEP) peptide family plays crucial roles in plant growth and stress response. However, little is known about this peptide family in Brassica species. Here, we performed a systematic analysis to identify the putative Brassica rapa L. CEP ( BrCEP ) gene family. In total, 27 BrCEP genes were identified and they were classified into four subgroups based on the CEP motifs sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Another sentinel gene involved in nitrogen remobilization and regulating plants’ nitrogen starvation response, GDH3 (Lezhneva et al, 2014; Safi et al, 2021), showed similar behavior (Table 1, Figure 5). On the other hand, CEP14 belonging to a family of peptides that induce nitrate transporter genes, resulting in nitrate acquisition in roots (Qiu et al, 2021), playing distinct roles in root and shoot development (Delay et al, 2013), was significantly induced at higher levels by NUF, and can contribute to the observed growth promotion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another sentinel gene involved in nitrogen remobilization and regulating plants’ nitrogen starvation response, GDH3 (Lezhneva et al, 2014; Safi et al, 2021), showed similar behavior (Table 1, Figure 5). On the other hand, CEP14 belonging to a family of peptides that induce nitrate transporter genes, resulting in nitrate acquisition in roots (Qiu et al, 2021), playing distinct roles in root and shoot development (Delay et al, 2013), was significantly induced at higher levels by NUF, and can contribute to the observed growth promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Another sentinel gene involved in nitrogen remobilization and regulating plants' nitrogen starvation response, GDH3 (Lezhneva et al, 2014;Safi et al, 2021), showed similar behavior (Table 1, Figure 5). On the other hand, CEP14 belonging to a family of peptides that induce nitrate transporter genes, resulting in nitrate acquisition in roots (Qiu et al, 2021), playing distinct roles in root and shoot development (Delay The advantage of NUF for the enhanced biomass yield of A. thaliana can be explained by the observed increased chlorophyll content of the NUF-treated seedlings (Figure 2C, 2F), also evident in the GO and KEGG pathway enrichment analysis where "photosynthesis" and "porphyrin metabolism" were enriched among genes significantly induced more under NUF compared to urea (Figure 3D).…”
Section: Discussionmentioning
confidence: 99%
“…The CEPD1 fat biosynthesis refers to the process of producing fatty acids and other types of lipids in living organisms. This process occurs downstream of the CEP (Carnitine/acylcarnitine transporter, EF-hand protein) pathway, which plays an important role in the transport of fatty acids into the mitochondria for energy production [68]. In the downstream process of fat biosynthesis, acetyl-CoA molecules are combined to form long-chain fatty acids through a series of enzymatic reactions [4,[8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…For example, knocking out the CEP gene in Arabidopsis resulted in increased primary root length and number of lateral roots [55,56]. Similarly, peptides such as BrCEP3 and BrCEP26 have been demonstrated to significantly enhance primary root growth in moss [57].…”
Section: The Role Of Small Peptides In Root Developmentmentioning
confidence: 99%
“…Specifically, IMA1 and IMA3 have been shown to enhance tolerance to cadmium (Cd) toxicity through the promotion of iron (Fe) accumulation (Figure 2) [98]. Furthermore, exposure to cadmium triggers an increase in the expression of BrCEP8 and Br-CEP19, indicating that BrCEPs may facilitate cadmium absorption in Brassicaceae, thereby augmenting Brassicaceae's tolerance to elevated Cd levels (Figure 2) [57]. Additionally, microRNA-encoded peptides (miPEPs) have been recognized for their regulatory role in plant tolerance to cadmium [99].…”
Section: The Role Of Small Peptides Under Other Stress Conditions And...mentioning
confidence: 99%